To study the utility of Cancer Ratio (Serum LDH: PLEURAL FLUID ADA RATIO) in identifying Malignant Pleural Effusion in Central Rural India - Chawla, Deepanshu; Ghewade, Babaji (International Journal of Psychosocial Rehabilitation, 2020)
In our study we have tried to evaluate the diagnostic possibility of lactate dehydrogenase level in serum, ADA in pleural fluid and their ratio in patients of effusion. This is study of pleural effusion(exudative) in patients admitted in Department of Respiratory Medicine LDH levels in serum and ADA levels in pleural fluid, their ratio which will be known as Cancer Ratio is expected to be elevated in cancer patients admitted with effusion. In our study, pleural fluid ADA is assumed to be negatively correlated with malignant effusion, on the other hand serum LDH with serum LDH: pleural fluid ADA ratio to be positively linked with patients of malignant pleural effusion. Serum LDH pleural fluid ADA ratio will distinguish malignant from non-malignant effusion. This can be done very early after admission or on outpatient basis.